Dihedral‐Angle‐Controlled Crossover from Static Hole Delocalization to Dynamic Hopping in Biaryl Cation Radicals. Issue 1 (29th November 2016) - Talipov, Marat R.; Navale, Tushar S.; Hossain, Mohammad M.; Shukla, Ruchi; Ivanov, Maxim V.; Rathore, Rajendra
Abstract: In cases of coherent charge‐transfer mechanism in biaryl compounds the rates follow a squared cosine trend with varying dihedral angle. Herein we demonstrate using a series of biaryl cation radicals with varying dihedral angles that the hole stabilization shows two different regimes where the mechanism of the hole stabilization switches over from (static) delocalization over both aryl rings to (dynamic) hopping. The experimental data and DFT calculations of biaryls with different dihedral angles unequivocally support that a crossover from delocalization to hopping occurs at a unique dihedral angle where the electronic coupling ( H ab ) is one half of reorganization ( λ ), that is, H ab = λ /2. The implication of this finding in non‐coherent charge‐transfer rates is being investigated. Abstract : Charge transport in biaryls : A dihedral‐angle‐dependent crossover of mechanisms from static delocalization to dynamic hopping in biaryl cation radicals was observed (see picture). The experimental data and DFT calculations unequivocally support that a crossover from delocalization to hopping occurs at a unique dihedral angle where the electronic coupling is exactly one half of the reorganization energy.